THE ROLE OF TEACHERS IN IMPROVING THE ABILITY TO READ AL-QUR'AN THROUGH LEARNING GHORIP MUSYKILAT AT TPQ AL-AHSAN TAMAN SARI - Nadifah, Himmatun; Arisanti, Kustiana; Laila Maghfiroh, Ummi (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
This study aims to describe the teacher's role in improving students' Qur'an reading ability through ghorib musykilat learning at TPQ Al-Ahsan Taman Sari. This research uses a descriptive qualitative method with a case study approach. Data were collected through observation, interviews, and documentation. The ghorib musykilat lessons are conducted after students complete Books 1 to 6 and Juz 27 of the Qiro'ati method, with teachers providing direct and intensive guidance. The learning focuses on difficult words and special reading marks such as imalah, isymam, tashil, and saktah. The Qiro'ati method is selected for its effectiveness in gradually and systematically building students' ability to read the Qur'an, enabling them to recognize various types of readings and marks. Teachers at TPQ act as educators, guides, facilitators, motivators, and evaluators. Besides teaching correct reading techniques, teachers instill Islamic values and create a supportive learning environment to boost students' confidence. The findings reveal that the comprehensive role of teachers significantly contributes to enhancing students' ability to read the Qur'an accurately and fluently, especially in understanding and pronouncing ghorib musykilat readings. The applied learning approach also improves students' motivation and discipline.